Transformation of Inclusive Education Policy and Practice Elementary School (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
This study examines the transformation of inclusive education policies and practices at a public elementary school in Bandung Regency through a descriptive qualitative approach. Inclusive education is essential to ensure equal access for all children, including those with special needs. Data were collected through observation, interviews with teachers and principals, and document analysis. The results show that policy transformation involves integrating inclusive principles into lesson plans, teacher training, and the enhancement of school facilities. This transformation has improved teaching effectiveness, student participation, and peer collaboration, creating a more supportive learning environment. Despite these positive outcomes, challenges persist, such as limited resources and low public awareness. To address these issues, the study recommends strengthening collaboration with local stakeholders, providing continuous teacher training, and increasing community involvement to sustain the progress of inclusive education implementation.